Vivekananda and Bengal Renaissance - Palit, Chittabrata (Indian Science Cruiser, 2012)
The impact of Western Culture threw India into the melting pot in the 19th Century. The people were suffering from intellectual bankruptcy and physical subordination and insignificance in relation to the European Culture and Civilization at the initial stage. They were obviously unaware of their past heritage and floated in the Western tide. This was the waning of medieval India’.